Synthesis and adsorption properties of sulfydryl-functionalized graphene oxide composite - Ming Yang; Xu Geng; Yongqing Xi; Fenfen Zhang (Desalination and Water Treatment, 2025)
The ions grasp effect of graphene oxide (GO) has long been researched for its rich chemical groups, however, the selective adsorption effect is limited. In order to further improve its adsorption capacity, sulfydryl-functionalized graphene oxide (SFGO) composite was prepared by (3-Mercaptopropyl) trimethoxysilane (MPTMS) with graphene oxide in one pot. Factors affecting its adsorption performance, including adsorbent dose, temperature, concentration of adsorbent solution, and adsorption time have been systematically investigated. Results revealed that SFGO can capture Ag (I) ions quickly with the maximal adsorption performance of 191.46 mg g−1. Sulfydryl group plays a crucial role in ultrahigh capture of Ag (I) ions from multi-element solution by chelating mechanisms. The adsorption isotherm fitting outcomes reveal that, the process conforms to the Langmuir isotherm pattern and obeys the pseudo-second-order kinetic pattern, it is spontaneous and exothermic. What’s more, as one of the precious metals, silver could be selectively extracted from complicated system through SFGO, revealing the superior selection of this material for precious metals. Therefore, the prepared SFGO will have broad prospects for environmental cleanup and recovery of precious metal due to it’s simple, economical and green synthesis method as well as promising efficiency.